Covering vertically aligned carbon nanotubes with a multiferroic compound. (February 2015) - Mahajan, Amit; Rodriguez, Brian J.; Saravanan, K. Venkata; Ramana, E. Venkata; Costa, Pedro M.F.J.; Vilarinho, Paula M.
Abstract: This work highlights the possible use of vertically-aligned multiwall carbon nanotubes (VA-MWCNTs) as bottom electrodes for microelectronics, for example for memory applications. As a proof of concept BiFeO3 (BFO) films were fabricated in-situ deposited on the surface of VA-MWCNTs by RF (radio frequency) magnetron sputtering. For in situ deposition temperature of 400 °C and deposition time up to 2 h, BFO films cover the MWCNTs and no damage occurs either in the film or MWCNTs. In spite of the macroscopic lossy polarization behaviour, the ferroelectric nature, domain structure and switching of these conformal BFO films was verified by piezo force microscopy. G type antiferromagnetic ordering with weak ferromagnetic ordering loop was proved for BFO films on VA-MWCNTs having a coercive field of 700 Oe.